Handling of Collective Violence by the Indonesian National Police (Case Study on the Handling of Conflicts Between Mass Organizations in Denpasar City) - I Gusti Ngurah Agung Arya Anjaya; Bayu Febrianto Prayoga (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
Social conflicts between mass organizations (Ormas) in Bali, particularly in Denpasar, frequently triggered collective violence between 2010 and 2017. Following interventions by the Denpasar Resort Police (Polresta Denpasar) starting in 2017, these incidents ceased, making the police’s efforts the focus of this research. This study examines collective violence between Ormas in Denpasar, the efforts of the Denpasar Resort Police in handling it, and the factors influencing the effectiveness of this conflict management. The research, conducted using a qualitative approach, revealed several findings, including that the root causes of collective violence were the militant attitudes of Ormas members and disputes over land. Handling that was not focused, tending to occur only at the time of the violent incidents, along with weak law enforcement, caused collective violence between Ormas to recur repeatedly. The existence of Ormas in Bali, exploited by political actors to gain votes or support, made it difficult for the police to break the cycle of violence. Comprehensive handling by the Denpasar Resort Police through criminal law enforcement efforts, non-penal measures, and the use of media succeeded in suppressing acts of collective violence by Ormas. The success of the handling by the Denpasar Resort Police cannot be separated from the leadership factors of the Bali Regional Police Chief, intervention in Ormas through government policies, the use of media, and community support. All these factors strengthened the handling efforts carried out by the Denpasar Resort Police.